# How do you simplify #(\frac { ( 4s ^ { 3} t ^ { - 2} ) ( 2t - 3u ^ { 5} ) } { 8u ^ { 7} } ) ^ { 2}#?

##### 2 Answers

Jul 21, 2017

#### Answer:

#### Explanation:

=

=

=

=

Jul 28, 2017

#### Answer:

#### Explanation:

Simplify inside the bracket first:

Square each factor in the bracket:

We could also square the binomial but there seems little point.

We would not be able to cancel any factors (there will be + and -signs.

There will not be like terms nor a common factor

The answer is already in factor form.